2004
DOI: 10.1161/01.cir.0000105724.30980.cd
|View full text |Cite
|
Sign up to set email alerts
|

Antirestenotic Effects of a Locally Delivered Caspase Inhibitor in a Balloon Injury Model

Abstract: Background-The precise role of arterial barotrauma-mediated apoptosis in causing restenosis is unclear. The purpose of this study was to determine if a link exists between angioplasty-mediated medial smooth muscle cell apoptosis and subsequent neointimal hyperplasia. Methods and Results-Bilateral iliac artery angioplasty was performed in 25 male New Zealand White rabbits. Simultaneous with balloon injury, each artery was treated locally with either the caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp(Ome)-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
1
26
1
1
Order By: Relevance
“…17,18 Moreover, the occurrence of smooth muscle cell apoptosis has been established in interventional procedures such as balloon angioplasty and stent implantation. 19,20 Unlike those previous studies, our report has shown that cells in the rabbit model undergo apoptosis within the aneurysm cavity, whereas cells in the wall of the aneurysm do not.…”
Section: Apoptosis In Endovascular Treatmentcontrasting
confidence: 88%
“…17,18 Moreover, the occurrence of smooth muscle cell apoptosis has been established in interventional procedures such as balloon angioplasty and stent implantation. 19,20 Unlike those previous studies, our report has shown that cells in the rabbit model undergo apoptosis within the aneurysm cavity, whereas cells in the wall of the aneurysm do not.…”
Section: Apoptosis In Endovascular Treatmentcontrasting
confidence: 88%
“…More importantly, the hVSMC response to bilirubin at the tested high physiological concentration does not cause apoptosis as shown by annexin V staining. This absence of apoptosis is significant given recent reports that apoptosis of VSMCs can trigger the development of neointima formation (20).…”
Section: Discussionmentioning
confidence: 83%
“…The lack of apoptosis in our model is likely important given recent reports that apoptosis of VSMCs can trigger the development of neointima formation. 29 Bilirubin peaks analyzed by HPLC in whole cell lysates increased significantly (AU 3.6Ϯ0.4 times versus control) measured 8 hours after biliverdin treatment. Considering the fact that the bilirubin and biliverdin effects on VSMC proliferation were independent of HO-1 expression, as tested in VSMCs from HO-1 knockout cells (data not shown), we assume the bilirubin we measured was converted from biliverdin rather than being generated by HO-1 induction.…”
Section: Discussionmentioning
confidence: 93%